Enhancing governance, accountability and transparency in islamic financial institutions : an examination into the audit of shari’a internal control system / Zurina Shafii and Supiah Salleh - Shafii, Zurina; Salleh, Supiah (Universiti Teknologi MARA Cawangan Selangor, 2010)
Governance of Islamic Financial Institutions (IFIs) is at the stage of infancy with most of the measures performed internally at the initiative of the management or industry regulated by the means of guidelines. Shari’a compliance reporting at the moment is not corroborated by the external independent parties. For that matter, investors and regulators know little how IFIs’ management exercises the measures to comply with the Shari’a. Lack of external corroboration and clear audit also reduces accountability and transparency that starve the decision makers of a better perspective on how to manage the risk of investment. Audit comprises of three elements namely audit of operations, internal control, and financial statement. The industry at the moment has to satisfy only the audit of operations by the way of Shari’a compliance audit or Shari’a review, without much done on the latter two that limits accountability and transparency of information being passed to the users. Without audit on the Internal Control System, the internal risk management is left unchecked. Little research has addressed the internal control measures in IFIs, thus the motivation of the authors to fill the gap. In this paper the authors highlighted the importance of external Shari’a audit to be carried out to check on the soundness of the internal control system in IFIs. A Shari’a internal control checklist was designed and adapted in two IFIs, namely Bank Islam Malaysia Berhad (BIMB) and Bahrain Islamic Bank (BIB). In terms of overall score, BIMB scored 97.6% whereas BIB 69.8%. The lower score obtained by BIB did not mean that BIB’s internal control system was not effective; instead it was because information was not disclosed in the annual report. BIMB managed to score above 90%, due to its full disclosure in the annual report. Increasing the level of information disclosed in the annual report will uphold the governance, transparency and integrity of the IFIs.